2014
DOI: 10.1111/pedi.12240
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of income to self-management and health outcomes in pediatric type 1 diabetes

Abstract: Low income has been established as a risk factor for poorer outcomes in youth with type 1 diabetes; however, the effect of moderate income has not been studied. The purpose of this secondary analysis of baseline data from a multi-site study was to compare glycemic control, self-management, and psychosocial outcomes [depression, stress, and quality of life (QOL)] at different income levels in adolescents with type 1 diabetes. Youth (n = 320, mean age = 12.3 + 1.1, 55% female, 64% white, mean A1C = 8.3 ± 1.4) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 39 publications
8
37
1
Order By: Relevance
“…This finding is consistent with previous studies which have demonstrated that low-income is a risk factor for poorer outcomes in adolescents with T1D and that adolescents from low-income families report greater general stress levels than their peers from higher income families [14,22,32]. We also found that adolescents from racially diverse backgrounds reported both higher general stress and diabetes-specific stress than their Caucasian peers.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies which have demonstrated that low-income is a risk factor for poorer outcomes in adolescents with T1D and that adolescents from low-income families report greater general stress levels than their peers from higher income families [14,22,32]. We also found that adolescents from racially diverse backgrounds reported both higher general stress and diabetes-specific stress than their Caucasian peers.…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis demonstrated that NEI was a significant predictor of HbA 1c , contributing to the body of evidence surrounding the impact of community‐level inequity and the social determinants of health on the clinical outcomes of individuals living with chronic diseases . These findings are also consistent with trends reported in studies that investigated the impacts of individual‐level factors such as income , socio‐economic status , and parental education/literacy on paediatric Type 1 diabetes management.…”
Section: Discussionsupporting
confidence: 85%
“…Wu et al [27] found that higher levels of caregiver support during adolescence were a protective factor from the expected decline in diabetes self-management adherence. Rechenberg et al [28] showed that socioeconomic status was associated with diabetes outcomes in adolescents with T1D. Those in higher income groups reported significantly lower HbA 1c , better diabetes problem-solving, lower levels of stress, and better QoL.…”
Section: Discussionmentioning
confidence: 99%